POTENSI KOEKSPRESI CHIMERIC ANTIGEN RECEPTOR (CAR) DAN GEN FOXP3 PADA SEL T REGULATORS SEBAGAI MODALITAS TERAPI PENATALAKSANAAN AUTOIMUN - Yulia Cahya Khasanah (Essence of Scientific Medical Journal, 2018)
Introduction: Autoimmune disease is immune response that damages self-tissues and disrupts physiologicalfunctions of the body. The prevalence of autoimmune diseases has continued to increase globally since World WarII. In US, this disease is the leading cause of death and commonly seen in women. Conventional autoimmunemedicine suppresses most of immune system and causes patients to be more susceptible to opportunistic infectionsand cancer. Based on these facts, therapeutic innovations that are specific to pathological immune cells are needed.Molecular therapy using stable, target-specific Tregs engineered is potential as the latest modality for autoimmunetherapy.Discussion: Autoimmune occurs when adaptive immune response attacks self-antigens. The autoimmunemechanism is then followed by activation of a large number of T cells. All activated T cells are controlled by Tregulators or Tregs. Tregs have weaknesses which are low selectivity and stability. For this reason, Tregengineering with selective receptor expression and Treg stabilizer is needed. The selective receptors that can bemodified with T cells are Chimeric Antigen Receptor (CAR). CAR is known to selectively inhibits pathologicalimmune responses and stops inflammation. CAR is combined with Treg stabilizer which gives the effect ofamplification and stabilization, that is Forkhead box P3 (FoxP3). FoxP3 is core protein that functions as the mainregulator of Tregs development and self-tolerance.Conclusion:CAR/FoxP3-Engineered Tregs express FoxP3 that have strong affinity for self-antigens through CARreceptors. The application of CAR/FoxP3-Engineered Tregs increases the selectivity and stability of Treg cells tosupress autoimmune.